Association between maternal near miss and sepsis in newborns cared for at the National Maternal Perinatal Institute, Lima 2016 - 2019 - De La Cruz Davila, Jean Pierre Eduardo (2021)
Introduction: Between 2012 and 2018, the prevalence of Extreme Maternal Morbidity (MME) in the National Maternal-Perinatal Institute (INMP) was 14.1 per 1000 live births, increasing over the years, which could cause repercussions in the newborn (NB) such as stillbirths, prematurity, low weight at birth, among others. Objective: To determine the association between MME and neonatal sepsis and to identify characteristics of the NB of mothers with and without MME and their morbidities. Materials and methods: Retrospective longitudinal study, in mothers exposed to MME (n = 378) and unexposed (n = 378), the outcome was followed in their NB in neonatal sepsis, of cases seen at the INMP between 2016 and 2019. We used the Stata program considering significant with p values <0.05. Results. 33% of newborns of children of mothers with MME presented neonatal sepsis (p <0.001), showing RR = 7.44 (95% CI 4.63-11.93) and RA = 1.59 (95% CI 0.88-2.84). Prematurity (p <0.001), cesarean section (p <0.001), hypertension prior to pregnancy (p <0.001), and meconium or fetid amniotic fluid (p <0.001) were associated with neonatal sepsis. In children of mothers with MME, 50.8% (p <0.001) had birth weight <2500 g, 23% (p <0.001) required resuscitation at birth, 12.4% (p <0.001) had hypoglycemia, 49.7% (p < 0.001) had a hospital stay> 7 days and 7.1% (p <0.001) died. Regarding the causes of MME, it was identified that 57.67% of mothers in this group presented hypertensive disorders during pregnancy, of which 33.94% of their children presented neonatal sepsis. Conclusions. In the analysis of frequencies and crude relative risk, it is possible to establish an association between the child of a mother with MME and the presentation of sepsis in the newborn.